2013
DOI: 10.1002/anie.201302245
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Magnetic Core–Shell Nanoparticles for Effective Stem‐Cell Differentiation and Imaging

Abstract: Special delivery! The title system, composed of a highly magnetic core surrounded by a thin uniform gold shell, has been synthesized and applied to the magnetically facilitated delivery of genetic material (siRNA or plasmid DNA) into neural stem cells (NSCs) for controlling their neural differentiation in a spatiotemporally controlled, biocompatible manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 44 publications
2
68
0
1
Order By: Relevance
“…2931 Additionally, our group as well as others have recently demonstrated that these MNPs can be further modified with a gold shell, thus having both magnetic and plasmonic properties that can be utilized for various biological applications including cell targeting, imaging, and chemotherapy. 32 …”
mentioning
confidence: 99%
“…2931 Additionally, our group as well as others have recently demonstrated that these MNPs can be further modified with a gold shell, thus having both magnetic and plasmonic properties that can be utilized for various biological applications including cell targeting, imaging, and chemotherapy. 32 …”
mentioning
confidence: 99%
“…These cores have previously been shown to have a significantly higher saturation magnetization when compared to conventional Fe 2 O 3 or Fe 3 O 4 magnetic nanoparticles (MNPs) [25]. As such, we first synthesized ZnFe 2 O 4 cores with a doping percentage of (Zn 0.4 Fe 0.6 )Fe 2 O 4 via the thermal decomposition of a mixture of metal precursors (zinc chloride, ferrous chloride, and ferric acetylacetonate) in the presence of oleic acid and oleylamine using a previously reported protocol that was modified by our group [23, 25]. Following core synthesis, an inert mSi shell was formed via the condensation of TEOS in the presence of a CTAB micelle template [26].…”
Section: Resultsmentioning
confidence: 99%
“…Thereafter, the MCNP complexes were mixed with Opti MEM (Life Technologies) and added to each well to attain the desired final concentration of plasmid/well. Subsequently, the cell culture plates were placed on a static Nd-Fe-B magnetic plate (OZ Biosciences, France) for 10 minutes (as optimized from previous reports) [23]. The culture plates were placed back into the incubator for 5 hrs and afterwards, the cells were washed with DPBS and the transfection medium was replaced with fresh growth medium.…”
Section: Methodsmentioning
confidence: 99%
“…4547 Third, the AuNP backbone of NanoScript can be replaced with other types of nanoparticles, such as upconverting nanoparticles and magnetic core–shell nanoparticles, for potential applications such as tracking gene regulation in real time through infrared imaging or magnetic resonance imaging (MRI), respectively. 43,48 Finally, the most advantageous feature of NanoScript is its tunable components, by simply redesigning the hairpin polyamide DBD sequence to target regulatory genes such as those involved in differentiation. However, it should be noted that, due to the short DBD targeting sequence, there is a possibility for interactions with off-target genes; hence, further optimization by designing DBDs with longer sequences to target longer DNA sequences would further enhance the NanoScript platform.…”
Section: Discussionmentioning
confidence: 99%